What if HCM Risk-SCD was assessed with CMR maximum LV wall thickness measurements?. (8th February 2021) - Neto, A; Oliveira, I; Cruz, I; Seabra, D; Pontes Dos Santos, R; Andrade, A; Azevedo, J; Pinto, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The HCM Risk-SCD estimates the risk of sudden cardiac death at 5 years in patients (pts) with hypertrophic cardiomyopathy (HCM). According to ESC Guidelines, in pts with a 5-year risk of SCD <4%, an implantable cardioverter defibrillator (ICD) is generally not indicated, in pts with a risk of 4 to less than 6%, an ICD may be considered and in pts with a 5-year risk ≥6%, an ICD should be considered. The association between the degree of LVH and sudden cardiac death (SCD) has been based on measurements of maximum LVWT by echocardiography which is part of HCM Risk-SCD score. However, cardiac magnetic resonance (CMR) has shown a superior resolution in characterization of cardiac structures, with additional role in SCD risk stratification. Whether measurements of LVWT by echocardiography and CMR are interchangeable has been brought to question. Purpose: We sought to evaluate the incidence of discrepant measurements of maximal LVWT between echocardiography and CMR and determine its implication in HCM Risk-SCD score and ICD indication. Methods: Unicentric, retrospective analysis of pts submitted to CMR who had HCM as definitive diagnosis, between 1/2013 and 9/2019. CMR and echocardiographic measures were compared, as well as HCM Risk-SCD score calculated with these values (maximum LVWT was the only variable that differed between measures). Subsequently, pts were divided in three groups according to HCM Risk-SCD score: pts with a 5-year risk of SCD <4% (G1), risk of 4 to less than 6% (G2) and risk ≥6% (G3). Results: Out of the 781 CMR studies evaluated, 59 pts were found to have HCM (7.6%) with mean age of 62 ± 11 years and female predominance (50.8%). 12 pts had obstructive phenotype (20.3%). Mean LVWT was 20.0 ± 4.6mm when measured by CMR and 18.8 ± 4.6mm by echo; when comparing the measures by echo with CMR, there was a positive correlation between them (p < 0.001; r 0.719). Mean HCM Risk-SCD was 2.80 ± 1.51% when measured by CMR and 2.69 ± 1.53% by echo; there was a positive correlation between these measures too (p < 0.001; r 0.963). Maximum LV thickness evaluated by CMR showed a positive correlation (p = 0.006, r 0.384) with the HCM risk-score assessed by CMR. Only 1 pt changed risk group with CMR measurement of maximum LVWT (from G1 to G2). Conclusion: In this cohort, there was a positive, linear relationship between maximum LVWT and HCM Risk-SCD score measured by CMR and echocardiogram. Only 1 pt changed risk stratification group (5-year risk of SCD <4% to 4 to less than 6%). Although CMR measurements, when interpreted correctly, are more precise compared with echocardiography, in this cohort there was no impact on the patient"s future clinical orientation regarding ICD implantation.